Exploring Consumers Satisfaction and General Public Image to the Tanzania Bureau of Standard (TBS): Expert Survey - Oreku, George S. (Archives of Business Research, 2022)
We investigated the level of consumers satisfaction to TBS service through the lens of research by undertaking survey on 9 pre-selected regions in Tanzania . The theoretical insights on comparing the overall service delivery with other rival organizations while identify area of focus to improve on TBS service delivery were identified. Mixed perception was observed among consumers which have led to negativity among the public and potential SMEs, as they view any interactions with the organization (TBS) as potential threat to their livelihood even though overall perception was satisfying. Further, the customers were made aware in understanding what TBS is all about in supporting and promoting their products to reach higher markets and international markets as standard goods. We compared the public opinions with our investigation approach using our tools of where contented consumers unintentionally participated and ultimately suggested and proposed ideal way forward.